Initial Experience of Video Capsule Endoscopy After Intestinal Transplantation. Issue 12 (December 2016) - Varkey, Jonas; Oltean, Mihai; Pischel, Andreas Bernd; Simrén, Magnus; Herlenius, Gustaf
Abstract : Background: Intestinal transplantation is a procedure which inflicts immunological and infectious complications that affect the transplanted graft, posing both diagnostic and therapeutic challenges. Video capsule endoscopy (VCE) offers easy access to the entire small intestine and presents itself as an interesting option. However, at present, no studies evaluating the usefulness of video capsule endoscopies in this setting have been published. Our aim was to evaluate the usefulness of VCE in detecting complications that arise after intestinal transplantation. Methods: We included 7 adult patients with either isolated intestine (n = 1) or multivisceral grafts (n = 6). These patients underwent 12 VCE between 2004 and 2015 at the Sahlgrenska University Hospital. The median age was 42 (21-67) years (4 women/3 men). VCE was used in clinical situations where the conventional diagnostic methods failed to provide answers to the clinical question. Results: Indications for the procedure were: suspicion of rejection (n = 4 examinations), gastrointestinal dysmotility (n = 4 examinations), high stomal output (n = 2 examinations), suspicion of lymphoproliferative disease in the transplanted graft (n = 1 examination), and clinical surveillance (n = 1 examination). The median time after transplantation for performing an examination was 740 (26-3059) days. VCE was useful in 83% of the examinations and the results influenced the planned management. The overall agreement between VCE findings and biopsies was moderate (κ = 0.54, P = 0.05) but increased when comparing the presence of inflammation/rejection (κ = 0.79, P < 0.001). Conclusions: VCE is a promising diagnostic method after intestinal transplantation. However, larger studies are needed to evaluate its potential risks and gains.